Synthesis and characterization of side-chain liquid-crystalline polyacrylates containing azobenzene moieties - Silong, S.; Lutfor, M.R.; Ab Rahman, M.Z.; Wan Yunus, W.M.Z. (2002)
Syntheses of novel liquid-crystalline polymers containing azobenzene moieties were performed by a convenient route with an acrylate backbone. The azobenzenes were key intermediates of the monomers, and side-chain liquid-crystalline polymers were prepared, that is, poly[α-(4-[(4-acetylphenyl)azo]phenoxy)alkyloxy]acrylates, for which the spacer length was 3 or 11 methylene units. In addition, poly[3(4-[(3,5-dimethylphenyl)azo]phenoxy)propyloxy]acrylate was prepared with a spacer length of 3 methylene units. The structures of the precursors, monomers, and polymers were characterized with Fourier transform infrared, 1H-NMR, and 13C-NMR techniques. The polymers were obtained by conventional free-radical polymerization with 2,2′-azobis-isobutyronitrile as an initiator. The phase-transition temperatures of the polymers were studied with differential scanning calorimetry, and the phase structures were evaluated with a polarizing optical microscopy technique. The results showed that two of the monomers and their corresponding polymers exhibited nematic liquid-crystalline behavior, and one of the monomers and its corresponding polymer showed smectic liquid-crystalline behavior. © 2002 Wiley Periodicals, Inc. J. Appl. Polym. Sci. 86.